Evaluation of the combined effect of factors influencing bowel preparation and adenoma detection rates in patients undergoing colonoscopy. Issue 1 (24th January 2019) - Tariq, Hassan; Kamal, Muhammad Umar; Sapkota, Binita; ElShikh, Fady; Pirzada, Usman Ali; Pullela, Nanda; Azam, Sara; Zhang, Aiyi; Baiomi, Ahmed; Abbas, Hafsa; Makker, Jasbir; Balar, Bhavna; et al.
Abstract : Background: Colonoscopy is a commonly used modality for screening and surveillance of colorectal cancer (CRC). Therefore, it is essential to have adequate bowel preparation (prep) for the procedure which depends on type of bowel regimens, diet before colonoscopy and timing of the procedure. Aims: The purpose of this study is to analyse the effect of multiple factors on adenoma detection rate (ADR) and prep quality of colonoscopy. This is the also the first study determining outcomes based on various combinations of diet, timing of the procedure and bowel prep regimens. Methods: This is a retrospective single-centre observational study. Data about diet before procedure, bowel prepprep regimen and timing of the procedure was collected for patients coming for screening colonoscopy. Results: Patients with split prep had higher good prep rates (73.8% vs 56.2%) and higher ADRs (34.2 % vs 29.9%) as compared with non-split prep. The good prep quality (65.8% vs 62.1%) and ADRs (31.9% vs 31.5%) were comparable in patients who received clear liquid diet as compared with low residue diet. The good results of bowel prep were obtained with split prep with either clear liquids or low residue diet irrespective of the timing of procedure. The poor prep was noticed in patients who underwent procedure in afternoon, with a low restrictive diet and non-split bowel regimen. Conclusions: The current study adds to our knowledge about the combined effect of multiple variables affecting the bowel prep quality and ADR. It is imperative to opt for the best combination required for colonoscopy, as this will influence the effectiveness of colonoscopies regarding timely cancer detection and prevention.